Gender, Access to Agricultural Extension, and Seed Sourcing among Small-scale Farmers in Uganda - Helaina M Curtin; Travis Reynolds; Daniel Tobin (Journal of International Agricultural and Extension Education, 2024)
Agricultural extension services have been vital for the development of the agricultural sector across the globe, providing information and support for farmers to improve their productivity and economic livelihoods. However, studies have shown that access to extension services may not be equitable, mediated by factors such as gender, remoteness, and type of production system. In Uganda, resource constraints and gender shape which small-scale farmers access extension services. This study uses data from two waves of the Ugandan National Panel Survey (collected with support from the World Bank through the Living Standards Measurement Study – Integrated Surveys on Agriculture) to investigate associations between access to agricultural extension services, gender, and participation in the formal seed sector among Ugandan small-scale farmers. Seed choices warrant consideration, given that they are an important input for crop-based production systems and have anchored many development efforts seeking to enhance the productivity of small-scale farmers. Findings suggest that small-scale farmers are more likely to purchase seeds through formal market channels and to use improved crop varieties after receiving agricultural extension services. We also find that female-headed households are significantly less likely to access extension or participate in the formal seed sector, limiting their access to seeds of improved varieties, providing further evidence that women farmers often confront more resource and social constraints than men. These findings emphasize the need for continued attention to how agricultural extension services can exacerbate existing social inequities and highlight the importance of identifying effective policy approaches to mitigate gender gaps in accessing agricultural resources.
Keywords: Uganda; seed systems; agricultural extension; NAADS; gender